EFFECT OF ORGANIZATIONAL CULTURE AND MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. YOROZU AUTOMOTIVE INDONESIA - Putra Alfandi Simangunsong (Jurnal Ilmu Manajemen Profitability, 2021)
Organizational Culture and Motivation are two important variables to measure the level of Organizational Culture and Motivation of employees. This study aims to examine the effect of these two variables on employee performance at PT. Yorozu Automotive Indonesia. This study took a sample of 130 employees at PT. Yorozu Automotive Indonesia with data collection techniques using a questionnaire. The analysis of this study used regression testing using SPSS as an analysis tool. The results of this study indicate that the two variables, Organizational Culture (X1) and Motivation (X2) have an effect on Employee Performance (Y) at PT. Yorozu Automotive Indonesia. The direct effect between variable X1 on variable Y was 53%, while the effect between variable X2 on Y was 21,5% and simultaneously variable X1 and variable X2 had an effect on variable Y by 42,2%.